Risk evaluation in a coffee supply chain - Napaporn Reeveerakul (2020)
Â© 2019 SERSC. Supply chain and risk mitigation are common concepts have been used in many fields of production or research. However, applying supply chain risks as a tool to mitigate overall risks from an agricultural perspective is very limited. This research aims to apply the SCOR concept while looking at risk evaluation by using the FMEA technique in coffee supply chain, northern Thailand. The qualitative and quantitative methods are also applied for collecting and analyzing data from supply chain stakeholders in coffee businesses. There are many types of critical risks, but only the high score risks, were considered in this paper. Results showed that in 5 core proceses of SCOR, 10 risk events were identified. Risk scores which lower than 20 have been ignored. Supply chain and value chain concept would certainly be a benefit to identify business processes in complex areas into the simple standard core processes. The implementing to agricultural area which is a complex system with several partners, can be easily without much changes in practice.